2022
DOI: 10.1590/1809-4392202101730
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of Amazonian gasteroid fungi (Agaricomycetidae, Phallomycetidae, Basidiomycota)

Abstract: The Amazon rainforest is the largest tropical rainforest in the world, with high biodiversity of organisms. Despite the increasing knowledge about fungal diversity in the last few years, many fungal taxa, including gasteroid clades, are still poorly known. Gasteroid fungi are recognized by the maturation of basidiospores inside the basidiomata and by the passive release of spores. We conducted a detailed survey of published data on the species that occur in Amazon forests. We confirmed the occurrence of 83 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…A portion of the basidiomycetes corresponds to gasteroid fungi, widely distributed in the tropics (Mueller et al, 2007), mainly in Brazil, where the diversity of the group increases every year (Accioly et al, 2019;Assis et al, 2022;Ferreira-Sá et al, 2021;Freitas et al, 2023;Santana & Couceiro, 2023). Studies with this group revealed the production of important substances with proven biological activity (Liu & Zhang, 2004;Dore et al, 2007;Coetze and Van Wyk, 2009), but there is a study gap regarding the discoloration of synthetic dyes.…”
Section: Trypan Blue Dye Discoloration In Solid Culture Mediummentioning
confidence: 99%
“…A portion of the basidiomycetes corresponds to gasteroid fungi, widely distributed in the tropics (Mueller et al, 2007), mainly in Brazil, where the diversity of the group increases every year (Accioly et al, 2019;Assis et al, 2022;Ferreira-Sá et al, 2021;Freitas et al, 2023;Santana & Couceiro, 2023). Studies with this group revealed the production of important substances with proven biological activity (Liu & Zhang, 2004;Dore et al, 2007;Coetze and Van Wyk, 2009), but there is a study gap regarding the discoloration of synthetic dyes.…”
Section: Trypan Blue Dye Discoloration In Solid Culture Mediummentioning
confidence: 99%
“…It has a cosmopolitan distribution (Kasuya et al 2012) and is considered one of the most diverse genera of gasteroid fungi, with 100 to 120 currently valid species worldwide (Zamora et al 2014). In Brazil, 67 species of Geastrum were recorded in the latest review by Accioly et al (2019), and 30 species were recorded in the Amazon (Assis et al 2022).…”
mentioning
confidence: 99%